PENGARUH MODEL CIRC TERHADAP KETERAMPILAN MEMBACA SISWA KELAS V SEKOLAH DASAR 05 - Halidjah, Melisa; Halidjah, Siti; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis purpose of this research was to analyze the effect of the application Cooperative Integrated Reading and Composition technique on the reading skills of the fifth grade students of the State Elementary School 05 Pontianak Kota. The method used in this research was an experiment with Quasi Experimental type of Nonequivalent Control Group Design. The sampling technique used Purposive Sampling. The technique used in data collection is measurement. Data collection tool used is a test. The result of data analysis are, the avarage score of the eksperiment class 74,18 learning outcomes and the control is 65,71. After the t-test is obtained tcount (3.20) > ttable (0.97) then Ha is accepted which indicates a difference significantly between the learning outcomes of the ekperimental class and the control clas, which means that there is an influence of the cooperative integrated reading and composition application on the reading skills of students. Based on the result of the calculating of the effect size (ES) obtained at 0,69 this showed that the application of the cooperative integrated learning model of integrated reading and composition provided a reasonably good influence on reading skills. Keywords: Cooperative Integrated Reading and Composition Technique,                                      Influence, Reading Skills